2013
DOI: 10.1111/1467-9248.12012
|View full text |Cite
|
Sign up to set email alerts
|

Rules, Strategies and Words: The Content of the 2010 Prime Ministerial Debates

Abstract: This article investigates the verbal content of the 2010 prime ministerial debates using computer-aided text analysis (CATA) and functional analysis. It seeks to provide reliable measures of what the leaders said, develop our theoretical understanding of televised debates in British elections, open up the 2010 debates for potential comparison with others, and provide additional evidence by which the democratic value of the debates might be assessed. The article demonstrates that the leaders focused more on pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…5 Partly for this reason, and partly because we were interested in their policy-information value, our analysis of the 2010 debates focused on the salience of key issues. We found limited evidence that leaders were able to emphasise those issues that advantaged them, in line with ownership theories (Allen et al, 2013). Brown, Cameron and Clegg did not consistently play to their issue strengths.…”
Section: Issues and Niche Partiesmentioning
confidence: 62%
See 2 more Smart Citations
“…5 Partly for this reason, and partly because we were interested in their policy-information value, our analysis of the 2010 debates focused on the salience of key issues. We found limited evidence that leaders were able to emphasise those issues that advantaged them, in line with ownership theories (Allen et al, 2013). Brown, Cameron and Clegg did not consistently play to their issue strengths.…”
Section: Issues and Niche Partiesmentioning
confidence: 62%
“…While it was not the primary focus of the article, this last point highlights the limits of applying salience theory to the analysis of leaders’ debates, or at least to the words of mainstream-party leaders. In an earlier study, we found that issue ownership did not help to predict the behaviour of party leaders (Allen et al, 2013). In our analysis of the 2015 debates, we again found little evidence that the major party leaders acted as if they ‘owned’ certain issues.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In a party conference context, for instance, Finlayson and Martin () explored the contribution of political speeches to understanding political institutions, ideologies and strategies, by analysing the rhetoric of Tony Blair's last speech as PM, while Pettit () focuses on identifying civic republicanism in Spain by analysing José Luis Rodríguez Zapatero's speeches as an PM. There are also some parallel studies on televised leadership debates using content analysis (Allen et al, ; Bastien ). In this article, we separate the party leader and the party MPs in a parliamentary context to compare their stance in the parliament and explore how this dilemma of representative versus responsible government is articulated in parliamentary discourse in these separate roles.…”
Section: Research Questions and Methodologymentioning
confidence: 99%
“…For example, a binary discourse of good and evil emerged in the speeches of U. S. presidents (Daghrir, 2013;Hughes, 2019). In addition to studies of democratic societies (Allen, Bara, & Bartle, 2013;Chung & Park, 2010), the speech of political ac tors in authoritarian states may inject the ru ling ideology to order, justify and legalize their policies rather than attempt to capture people's hearts (Carreon & Svetanant, 2017, p. 640). Previous studies focused mainly on Iranian presidents' speeches delivered at official functions (e. g., presidential elections and United Nations General Assembly), and they generally reinforce the hegemonic discourse in Iran that emphasizes national pride and empowerment and is based on hostility toward the U. S. (Alemi, Tajeddin, & Rajabi Kondlaji, 2018;Jahangiry & Fattahi, 2012).…”
Section: Language and Discourse Of Politicians' Speechesmentioning
confidence: 99%